Leadership-Management preferences at the workplace and across cultures in China - Yang, Zihao (2013)
This study aims to cross-culturally validate Lek, Chioang and Ang [2012] findings on leadership-management preferences (LMP), and to explore the relationship between LMP and leadership-management competencies (LMC) as well as the relationship between LMC and job performance. Paper-and-pencil surveys were administered to employees and their immediate superiors from 5 organisations in Tianjin, China. The surveys were developed by translating various existing measures from English to Mandarin. Back-translation was also carried out to ensure the accuracy of the translation.